Research on Urban Parking Space Sharing Mode Based on Multi-Source Data Fusion - Jianqiang Xiong (Forest Chemicals Review, 1970)
The rapid increase of urban car ownership and the serious backwardness of urban parking facilities planning and management technology have led to the increasingly prominent problem of urban parking difficulties. Aiming at the problem of urban parking difficulty, this paper put forward a method of urban parking sharing based on multi-source data fusion. In the research, a platform system of urban parking sharing based on multi-source data fusion was constructed, and the adjustment method and dynamic adjustment mechanism of parking sharing conflict were proposed. In this method, parking space sharing period, sharing price and sharing distance are used as the basis of multi-source data. Then, according to the parking space sharing demand, the corresponding idle parking space sharing information is obtained through cloud computing and analysis to solve the personalized parking demand. The research in this paper provides theoretical support for the urban parking space sharing system, and plays a positive role in improving the utilization efficiency of parking spaces, alleviating the contradiction between supply and demand of urban parking, reducing urban traffic congestion, energy saving and emission reduction, and improving the efficiency of urban economic and social operation.